Leptospirosis with MODS -Cause of Concern! - Hamza Ismaeel, Valeed Bin Mansoor, Zohaib Akram , Hamza Ismaeel, Valeed Bin Mansoor, Zohaib Akram (Journal of Rawalpindi Medical College, 2020)
Introduction: A clear majority of people in Pakistan reside in small villages and hamlets. Predominantly a large chunk of the population is employed in Agrarian Rural economy. Leptospirosis is an emerging zoonotic, often overlooked as a cause of MODS, CRF and ESRD, presenting as ARF, Acute Liver Failure and other varied symptomatology. Contact with livestock and other risk factors is thus inevitable, which this report highlights. Purpose of our case report is to bring into consideration and address Weil’s disease as an often-missed diagnosis, especially in patients with an agrarian background. We present an interesting case of Weil’s disease with MODS in a farmer, who also had a prior history of multiple comorbidities such as Diabetes Mellitus and Smoking history, where in due diligence was undertaken-with timely diagnosis of Leptospirosis; instituting dialysis and antibiotics. Patient was advised upon discharge with instructions for follow-up especially to address and manage another anomaly of ESRD, which has also been observed years after initial Leptospirosis infection. Abbreviations used: ESRD (End stage Renal Disease), MOF (Multi Organ Failure)/MODS (Multi Organ Dysfunction Syndrome), ARF (Acute Renal Failure), CRF (Chronic Renal Failure).